Synthesis and characterization of zinc oxide nanoparticles by using polyol chemistry for their antimicrobial and antibiofilm activity - Mahamuni, P. P.; Patil, P. M.; Dhanavade, M. J.; Badiger, M. V.; Shadija, P. G.; Lokhande, A. C.; Bohara, R. A. (Biochemistry and Biophysics Reports, 2019)
The present investigation deals with facile polyol mediated synthesis and characterization of ZnO nanoparticles and their antimicrobial activities against pathogenic microorganisms. The synthesis process was carried out by refluxing zinc acetate precursor in diethylene glycol(DEG) and triethylene glycol(TEG) in the presence and in the absence of sodium acetate for 2 h and 3 h. All synthesized ZnO nanoparticles were characterized by X-ray diffraction (XRD), UV visible spectroscopy (UV), thermogravimetric analysis (TGA), fourier transform infrared spectroscopy (FTIR), field emission scanning electron microscopy(FESEM), transmission electron microscopy (TEM) and energy dispersive X-ray spectroscopy (EDX) technique. All nanoparticles showed different degree of antibacterial and antibiofilm activity against Gram-positive Staphylococcus aureus (NCIM 2654)and Gram-negative Proteus vulgaris (NCIM 2613). The antibacterial and antibiofilm activity was inversely proportional to the size of the synthesized ZnO nanoparticles. Among all prepared particles, ZnO nanoparticles with least size (~ 15 nm) prepared by refluxing zinc acetate dihydrate in diethylene glycol for 3 h exhibited remarkable antibacterial and antibiofilm activity which may serve as potential alternatives in biomedical application.